Company stock in defined contribution plans and stock market returns - Heejin Park; Jung Hee Noh; Kyojik "Roy" Song (Global Business & Finance Review (GBFR), 2021)
Purpose: We examine whether employee ownership in DC plans are explained by either shared capitalism or managerial entrenchment motives. Design/methodology/approach: We calculate the average monthly risk-adjusted return (alpha) of each portfolio by sorting firms into six portfolio groups based on the percentage of employer stock in market value of equity. Findings: We find that the zero-investment strategy of buying a portfolio without employee ownership and selling a portfolio with the largest employee ownership earns 1.32% of alpha per month. Further, we provide evidence that portfolios with higher employee ownership experience greater distress risk. Research limitations/implications: These findings suggest that the capital market significantly overvalues firms with employee ownership in DC plans, supporting managerial entrenchment motives. Originality/value: To the extent that there has been no research to provide time series evidence on the relation between employee ownership and stock returns, this study's novelty is that it could explain the mixed results presented by previous literature.
Keywords: 650; Defined contribution plan; Employee ownership; Shared capitalism; Managerial entrenchment; Alpha